Ecosystem services, targets, and indicators for the conservation and sustainable use of biodiversity. Issue 9 (5th October 2011) - Perrings, Charles; Naeem, Shahid; Ahrestani, Farshid S; Bunker, Daniel E; Burkill, Peter; Canziani, Graciela; Elmqvist, Thomas; Fuhrman, Jed A; Jaksic, Fabian M; Kawabata, Zen'ichiro; Kinzig, Ann; Mace, Georgina M; et al.
Abstract : After the collective failure to achieve the Convention on Biological Diversity's (CBD's) 2010 target to substantially reduce biodiversity losses, the CBD adopted a plan composed of five strategic goals and 20 "SMART" (Specific, Measurable, Ambitious, Realistic, and Time‐bound) targets, to be achieved by 2020. Here, an interdisciplinary group of scientists from DIVERSITAS – an international program that focuses on biodiversity science – evaluates these targets and considers the implications of an ecosystem‐services‐based approach for their implementation. We describe the functional differences between the targets corresponding to distinct strategic goals and identify the interdependency between targets. We then discuss the implications for supporting research and target indicators, and make several specific suggestions for target implementation.